2011
DOI: 10.2500/aap.2011.32.3440
|View full text |Cite
|
Sign up to set email alerts
|

Response to ecallantide treatment of acute attacks of hereditary angioedema based on time to intervention: Results from the EDEMA clinical trials

Abstract: Hereditary Angioedema (HAE) is a rare, debilitating, genetic disorder characterized by acute attacks of edema without urticaria. Ecallantide, a direct plasma kallikrein inhibitor, is approved for treatment of acute HAE attacks. This article addresses the efficacy of ecallantide in the treatment of moderate-to-severe attacks of HAE based on time to treatment. A post hoc integrated analysis of the EDEMA4 and EDEMA3-DB clinical trials was performed based on the time to patient's treatment, defined as the time fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Early treatment with C1‐INH concentrate, ecallantide, or icatibant provides a better treatment response than late treatment. Early treatment is associated with a shorter time to resolution of symptoms and shorter total attack duration regardless of attack severity . As early treatment is facilitated by self‐administration, all patients with HAE‐1/2 should be considered for home therapy and self‐administration training .…”
Section: Therapymentioning
confidence: 99%
“…Early treatment with C1‐INH concentrate, ecallantide, or icatibant provides a better treatment response than late treatment. Early treatment is associated with a shorter time to resolution of symptoms and shorter total attack duration regardless of attack severity . As early treatment is facilitated by self‐administration, all patients with HAE‐1/2 should be considered for home therapy and self‐administration training .…”
Section: Therapymentioning
confidence: 99%
“…Patients in this trial reported a mean decrease of symptom score at 4 h of 0.81 on Ecallantide vs. 0.37 on placebo (P = 0.01) [35]. A post hoc integrated analysis of the EDEMA4 and EDEMA3 clinical trials showed that change from baseline in MSCS and TOS was significantly better with ecallantide vs. placebo for patients treated > 2-4 h after symptom onset (n = 46, P = 0.002, P = 0.003) and > 4-6 h after onset of symptoms (n = 47, P = 0.044, P = 0.043) [36].…”
Section: Contact System Modulatorsmentioning
confidence: 99%
“…HAE attack treatments are most effective when administered early. [5][6][7] Although patients are dependent upon ª 2016 British Association of Dermatologists healthcare providers for the administration of ondemand treatment, many have reported not seeking treatment in a hospital as a result of previous inappropriate treatment, e.g. for histamine-induced angiooedema.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is most effective when administered early in the course of an HAE attack . Home‐based self‐administration of C1 inhibitor or icatibant for the on‐demand treatment of attacks reduces attack duration and treatment‐associated costs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation